2020
DOI: 10.3168/jds.2019-17476
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the production, reproduction, and functional traits of Holstein-Friesian, Jersey × Holstein-Friesian, and Norwegian Red × (Jersey × Holstein-Friesian) cows in pasture-based systems

Abstract: Pasture-based production systems typically require highly fertile, healthy, and robust genetics, with greater emphasis on milk solids (MSo; kg of fat + protein) production as opposed to milk yield. This study assessed milk production, production efficiency, reproductive performance, body weight (BW), body condition score, and functional traits in 3 different dairy cow genotypes: Holstein-Friesian (HF), Jersey × Holstein-Friesian (JEX), and Norwegian Red × (Jersey × Holstein-Friesian) (3-way). The 3 genotypes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
4
14
0
1
Order By: Relevance
“…Additionally, the higher value of milk from crossbred animals similar to those used in this study has been reported before, in particular for Jersey crossbreds due to their higher milk fat and protein content compared with HF cows (Heins et al, 2008;Prendiville et al, 2011a;Coffey et al, 2016) and also for Norwegian Red crossbred animals (Heins et al, 2006;Walsh et al, 2008;Ferris et al, 2014). Although the difference in net profit per cow in this study is less than the €184 reported by Prendiville et al (2011b), there is still benefit to crossbreeding within pasturebased production systems, both economically and in terms of milk production efficiency (McClearn et al, 2020). The EBI reflects the relative contributions of the different traits to overall profitability.…”
Section: Influence Of Cow Genotype On Farm Profitabilitysupporting
confidence: 70%
“…Additionally, the higher value of milk from crossbred animals similar to those used in this study has been reported before, in particular for Jersey crossbreds due to their higher milk fat and protein content compared with HF cows (Heins et al, 2008;Prendiville et al, 2011a;Coffey et al, 2016) and also for Norwegian Red crossbred animals (Heins et al, 2006;Walsh et al, 2008;Ferris et al, 2014). Although the difference in net profit per cow in this study is less than the €184 reported by Prendiville et al (2011b), there is still benefit to crossbreeding within pasturebased production systems, both economically and in terms of milk production efficiency (McClearn et al, 2020). The EBI reflects the relative contributions of the different traits to overall profitability.…”
Section: Influence Of Cow Genotype On Farm Profitabilitysupporting
confidence: 70%
“…McClearn et al (2020a,b) reported on total lactation milk production, and reproductive and economic performance of the 3 genotypes used in this experiment and found similar MSo yield between HF and JEX, HF, and 3WAY but that 3WAY had lower MSo yield than JEX. Reproductive performance of all 3 genotypes was similar (McClearn et al, 2020a) but JEX were the most profitable on a per hectare basis, followed by 3WAY and HF (McClearn et al, 2020b). This paper investigated the differences in DMI and milk production efficiency between the 3 genotypes to further elucidate why the differences observed by Mc-Clearn et al (2020a,b) occurred.…”
Section: Discussionmentioning
confidence: 87%
“…Three cow genotypes were used for this experiment: HF, JEX, and 3WAY (McClearn et al, 2020a). Briefly, during the experiment HF cows were either mated with a HF sire to produce a HF cow or a Jersey sire to produce F 1 (first cross generation) crossbred JEX cows.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in F 1 crosses, 50% of genes comes from another breed than HO, but this other breed is not specified in our method. However, depending on whether it is Swiss Brown or Jersey, the characteristics provided by the breed may differ [ 37 ], and therefore, the performance of resulting cross with HO may differ too [ 28 , 43 ]. This may explain why we did not observe significant differences between F 1 and G 2 or between F 1 and HO for some traits.…”
Section: Discussionmentioning
confidence: 99%